2021
DOI: 10.1093/brain/awab042
|View full text |Cite|
|
Sign up to set email alerts
|

Medial septal GABAergic neurons reduce seizure duration upon optogenetic closed-loop stimulation

Abstract: Seizures can emerge from multiple or large foci in temporal lobe epilepsy, complicating focally targeted strategies such as surgical resection or the modulation of the activity of specific hippocampal neuronal populations through genetic or optogenetic techniques. Here, we evaluate a strategy in which optogenetic activation of medial septal GABAergic neurons, which provide extensive projections throughout the hippocampus, is used to control seizures. We utilized the chronic intrahippocampal kainate mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 83 publications
2
25
0
Order By: Relevance
“…Once seizures have already developed (during ictal states) ( Figure 2iii ), the responsive MS electrical (or optogenetic) stimulation at a fixed frequency (open-loop) cannot effectively stop seizures (but see Miller et al, 1994 ; Hristova et al, 2021 ). Rather, electrical stimulation of the MS at a fixed frequency worsens symptoms of TLE seizures; it induces secondary generalization of partial seizures ( Figure 3 ).…”
Section: The Medial Septum As a Target For Deep Brain Stimulation For Epilepsy Control And Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…Once seizures have already developed (during ictal states) ( Figure 2iii ), the responsive MS electrical (or optogenetic) stimulation at a fixed frequency (open-loop) cannot effectively stop seizures (but see Miller et al, 1994 ; Hristova et al, 2021 ). Rather, electrical stimulation of the MS at a fixed frequency worsens symptoms of TLE seizures; it induces secondary generalization of partial seizures ( Figure 3 ).…”
Section: The Medial Septum As a Target For Deep Brain Stimulation For Epilepsy Control And Beyondmentioning
confidence: 99%
“…The MS stimulation has been shown to be effective in rodent models of TLE with and without obvious damages of HPC (chronic intrahippocampal kainite model, HPC electrical kindling model), which correspond to human epilepsy with and without sclerosis ( Wang et al, 2020b , 2021 ; Hristova et al, 2021 ; Takeuchi et al, 2021a ). In addition, the MS stimulation has been shown to improve cognitive alterations, which are often comorbid in epilepsy, in animal models of TLE ( Izadi et al, 2019 ; Wang et al, 2021 ).…”
Section: The Medial Septum As a Target For Deep Brain Stimulation For Epilepsy Control And Beyondmentioning
confidence: 99%
“…Even when the pacemaker neurons that drive the rhythm are found, finding the temporal window(s) during which they set the pace and evoke a behavioral output can be difficult. "Closedloop" optogenetic control of neurons based on ongoing activity was suggested several years ago (Grosenick et al, 2015), and has proven efficient at controlling seizures in rodents (Sorokin et al, 2017;Hristova et al, 2021). This approach could be used for manipulating neuronal activity selectively during relevant periods, such as when a specific oscillatory power exceeds or goes below a critical value (Van De Ven et al, 2016;Nicholson et al, 2018).…”
Section: Future Directionsmentioning
confidence: 99%
“…The 5 Hz stimulation yielded the most significant effects on all measurements ( Wang et al, 2021 ). A slice preparation experiment showed that directly stimulating the GABA-ergic neurons in the medial septum (MS) achieves the same effect ( Hristova et al, 2021 ). The results coincide with the already established role of the MS that is the generation and input of theta oscillations to the hippocampus ( Buzsáki, 2002 ; Watson et al, 2019 ).…”
Section: Pathological Oscillationsmentioning
confidence: 99%